PENGARUH KOSENTRASI ZAT PENGATUR TUMBUH INDOLE-3 ACETIC ACID DAN BENZYL AMINO PURINE TERHADAP MULTIPLIKASI TANAMAN PISANG CAVENDISH (Musa cavendishii) SECARA IN VITRO - Azam Muttaqien; Susiyanti .; Yuhelsa Putra (Jurnal Agroekoteknologi, 2016)
The aims of this research were to identify the effect of concentration growth regulator IAA and BAP as the basic MS medium against multiplication of banana plants by in vitro. The experiment  was   carried  out  at   Laboratory  of   Biotechnology,  Faculty  of Agriculture, University of Sultan Ageng Tirtayasa from November 2013 to May 2014. The experiment used Completely Randomized Design which arranged in with two factors. The first factor was the concentration of growth regulators IAA which consisted of 4 levels (0 mg/L, 0.1 mg/L, 0.2 mg/L, 0.3 mg/L). The second factor was growth regulator BAP which consisted of 4 levels (0 mg/L.2 mg/L, l.4 mg/L, 1.6 mg/L), so that there were 16 treatment combinations, and repeated 3 times. The variables observed were number of shoots and growing percentage of the plant. The results showed that there was significantly interaction in number of shoot in 3 WAP. The best treatment was I1B1 (IAA 0,1 mg/L dan BAP 2 mg/L) for the number of shoot in 5 WAP. Keywords: IAA, BAP, Banana, Multiplication